Risk Factors of SARS-CoV-2 Antibodies in Arapahoe County First Responders—The COVID-19 Arapahoe SErosurveillance Study (CASES) Project. Issue 3 (March 2021) - Sabourin, Katherine R.; Schultz, Jonathan; Romero, Joshua; Lamb, Molly M.; Larremore, Daniel; Morrison, Thomas E.; Frazer-Abel, Ashley; Zimmer, Shanta; Kedl, Ross M.; Jaenisch, Thomas; Rochford, Rosemary
Abstract : Objectives: Define the seroprevalence and risk factors for SARS-CoV-2 antibodies in Arapahoe County, Colorado first responders (eg, law enforcement, human services, fire departments). Methods: Two hundred sixty four first responders were enrolled June to July 2020. SARS-CoV-2 seropositivity was defined as detection of immunoglobulin G (IgG) antibodies to both spike receptor binding domain and nucleocapsid in venous blood by validated enzyme-linked immunosorbent assay. We compared risk factors for being seropositive versus seronegative. Results: 4% (11/264) were SARS-CoV-2 seropositive. Seropositive participants were significantly more likely to have lung disease (% seropositive, % seronegative; P -value) (36%, 8%; P = 0.01), prior SARS-CoV-2/COVID-19 testing (36%, 8%; P ⩽ 0.01), a prior positive result (18%, less than 1%), and to believe they previously had COVID-19 (64%, 15%; P < 0.01). Only 15% of those believing they had COVID-19 had anti-SARS-CoV-2 antibodies. Conclusions: Human services employees and individuals with lung disease are at SARS-CoV-2 exposure risk. Few individuals believed they had COVID-19 had prior exposure. Abstract : Supplemental Digital Content is available in the text